Nobiletin protected against hypertrophic cardiomyopathy via targeting PPARα - Zhou, Kewei; Chen, Chang; Cai, Hexin; Lian, Zuqian; Wang, Luping; Li, Qinghuo; Wang, Cancan; Wu, Xiaoqian; Wang, Panxia (Frontiers in Pharmacology, 2025)
BackgroundHypertrophic cardiomyopathy is an independent risk factor for heart failure. Citrus reticulata (C. reticulata) is a traditional Chinese medicine with a variety of chemical components and pharmacological effects. The mechanisms of C. reticulata for treating hypertrophic cardiomyopathy are still unclear.MethodsIn this study, we used network pharmacology techniques combined with bioinformatics analysis and identified the active ingredient in C. reticulata to protect against hypertrophic cardiomyopathy. We analyzed the Gene Expression Omnibus (GEO) database from human heart tissue with hypertrophic cardiomyopathy to reveal the potential targets. Finally, molecular docking and in vitro validation were used to reveal the binding of the potential targets and the main active component of C. reticulata.ResultsOur results revealed that there are five main active ingredients of C. reticulata (nobiletin, naringenin, sitosterol, 5,7-dihydroxy-2-(3-hydroxy-4-methoxyphenyl) chroman-4-one, and citromitin). By analyzing the intersecting genes between C. reticulata and hypertrophic cardiomyopathy, 40 hub genes were obtained. Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis indicated that the responses to oxidative stress and fatty acids were the main pathways for C. reticulata to act against hypertrophic cardiomyopathy. The protein–protein interaction analysis results showed that the main active ingredients of C. reticulata were nobiletin and naringenin, while peroxisome proliferator-activated receptors (PPAR)α might be the potential targets of C. reticulata in treating hypertrophic cardiomyopathy. The molecular docking results showed that the main active ingredient, nobiletin, could bind to PPARα with a strong hydrogen-bonding interaction force. In vitro results validated that nobiletin might directly bind to PPARα, thereby increasing the expression of lipid metabolism-related genes and relieving hypertrophic responses of cardiomyocytes.ConclusionThe nuclear receptor PPARα might be the potential endogenous receptor of the active ingredients of C. reticulata.